2016
DOI: 10.1259/bjr.20160004
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary computed tomography findings in patients with chronic aspiration detected by videofluoroscopic swallowing study

Abstract: CT findings of aspiration are very important, as pulmonary symptoms may be the first manifestation of this disorder. Knowledge of these findings is essential to enable the early diagnosis of aspiration disorders and prevent lung damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“… 18 , 19 One of the studies demonstrated a higher frequency of findings in the right lung, 17 and two found changes that were more prevalent in lower lung zones. 16 , 18 In the study by Simonelli et al, 15 it was not possible to describe the proportion of findings, because they were reported by degree of aspiration. It is of note that, in two studies, aspirators and non-aspirators were compared.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“… 18 , 19 One of the studies demonstrated a higher frequency of findings in the right lung, 17 and two found changes that were more prevalent in lower lung zones. 16 , 18 In the study by Simonelli et al, 15 it was not possible to describe the proportion of findings, because they were reported by degree of aspiration. It is of note that, in two studies, aspirators and non-aspirators were compared.…”
Section: Resultsmentioning
confidence: 98%
“…Most of the studies evaluated in this review had a retrospective, cross-sectional design. 15 - 18 The sample characteristics varied. The patients studied had laryngeal cancer, 15 acute pneumonia associated with dysphagia, 16 or chronic aspiration, 17 , 18 and a study of healthy subjects assessed the presence or absence of aspiration.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations